Fibrous Dysplasia in the Maxillary Bone: The Early Diagnosis of Progressive Pain with Facial Asymmetry - Liemiyah, Rikha; Dewi, Anna Mailasari Kusuma; Antono, Dwi; Nugroho, Nur Iman; Muyassaroh, Muyassaroh; Kusumaningrum, Lely; Arsita, Cynthia (http://dharmais.co.id/, 2025)
Introduction: Fibrous dysplasia (FD) is a genetic, non-familial skeletal disorder, where in medullary bone is replaced by fibro-osseus tissue. Ninety percent of FD instances involve the craniofacial region, which usually involves one or more bones. The ethmoid, sphenoid, frontal, maxillary, and temporal bones are the most affected, but the maxilla is most affected. Misdiagnosis and inappropriate diversity in investigations and therapies are frequently caused by the disease’s rarity and varying presentation to other specialties. This study aims to analyze the signs, symptoms, and laboratory-radiology examinations of suspected FD patients at Dr. Kariadi General Hospital Semarang so that it can increase the sensitivity of medical personnel in establishing this diagnosis based on the symptoms and signs complained of by the patient.Case Presentation: A case series study assessing three patients diagnosed with FD of the maxillae between January and December 2021 at Dr. Kariadi General Hospital, Semarang. The study found 3 patients diagnosed with FD of the maxillae consisting of 2 males and 1 female. The initial complaints reported in all patients were progressive facial pain, thick sensation in the cheek area, and asymmetrical facial shape due to abnormal protrusions. Physical examination found an increase in facial volume with a hard consistency. CT scan evaluation obtained a sclerotic image with ground glass opacity in two patients and hyperostosis in one patient. Surgery with the Weber Ferguson technique was undergone by two patients, while one patient underwent the Weber Ferguson Technique + Zoledronic Acid for 6 cycles. Both patients who underwent Weber Ferguson technique surgery experienced recurrence related to symptoms in the form of pain and increased volume in the facial area within 2–4 weeks after surgery.Conclusions: Patients with complaints of progressive pain and asymmetrical shape in the facial area and physical examination found an increase in facial volume with hard consistency should be able to increase the suspicion of medical personnel regarding the diagnosis of FD. Further radiological examination with tissue histopathology should be performed to rule out or confirm the diagnosis of FD.